The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.20885/ejem.vol14.iss2.art2
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the asymmetry between the exchange rate and domestic production in South Asian Economies: Evidence from Nonlinear ARDL Approach

Abstract: : Many of the early studies that investigate the impact of exchange rate movements on domestic production report mixed findings in terms of the effect on economic growth. However, the majority of these studies had were limited in that they relied on a prior assumption of linear adjustment of the exchange rate fluctuations toward domestic output. We suspect that a prior assumption of linearity may mask the empirical results. We, therefore, bring nonlinearity into the adjustment process through the partial sum a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…For instance, according to Bahmani‐Oskooee, Halicioglu, and Mohammadian (2018), both PREX and NREX have expansionary impacts on domestic output. Iqbal et al (2022) provide substantial evidence demonstrating the asymmetric impacts of exchange rate variations on domestic output, both in the short and long terms, across all economies studied. According to Bahmani‐Oskooee and Arize (2020), results differ by country.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, according to Bahmani‐Oskooee, Halicioglu, and Mohammadian (2018), both PREX and NREX have expansionary impacts on domestic output. Iqbal et al (2022) provide substantial evidence demonstrating the asymmetric impacts of exchange rate variations on domestic output, both in the short and long terms, across all economies studied. According to Bahmani‐Oskooee and Arize (2020), results differ by country.…”
Section: Resultsmentioning
confidence: 99%
“…They further find that appreciation negates domestic production for some of the sample countries while a depreciation exerts no impact. Iqbal, et al (2022) using the nonlinear ARDL model and data from 1980 to 2019 for South Asian countries, explored the impact of exchange rate changes on domestic production. They decomposed the exchange rate into depreciation and appreciation to introduce nonlinearity into the adjustment process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most of the earlier studies used models that assumed the relationship between the real effective exchange rate and economic growth is linear. However, recent studies, including Iqbal, et al (2022), Bahmani-Oskooee and Arize (2020), and Eroğlu and Olayiwola (2023) have shown that the relationship between the real effective exchange rate and national output is better modeled in a nonlinear fashion. The present study contributes to the debate on the impact of the real effective exchange rate on economic growth by employing the nonlinear panel ARDL-PMG estimator proposed by Shin et al (2014).…”
Section: Introductionmentioning
confidence: 99%